Driving Factors of the Marine Capture Fishery Production Economy and Resource Sustainability - Muhammad Ikbal; Rahmatia Yunus; Anas Iswanto (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose: This study examines the effects of fleet size, number of fishermen, and the Fishermen’s Exchange Rate on marine capture fishery production, with fishing households and fish consumption as mediating variables. Design/methodology/approach: This study uses panel data from 33 provinces during 2010–2020 and applies regression-based path analysis to test both direct and indirect effects among the variables. Findings/Results: The results show that fleet size and number of fishermen have positive effects on fishery production, while the Fishermen’s Exchange Rate has a significant negative effect. Fishing households show a mediating role depending on production and distribution conditions, while fish consumption contributes to production through demand pressure. Originality/Value: This study highlights the interaction between economic, household, and demand-side factors in shaping fishery production. The findings suggest that fisheries policy should integrate productivity, distribution efficiency, and sustainability considerations.